Dedicated Barrett's surveillance sessions managed by trained endoscopists improve dysplasia detection rate - Ooi, Joanne; Wilson, Patrick; Walker, Giles; Blaker, Paul; DeMartino, Sabina; O’Donohue, John; Reffitt, David; Lanaspre, Effie; Chang, Fuju; Meenan, John; Dunn, Jason M. (Endoscopy, 2017)
Background and study aim Barrett’s esophagus (BE)-associated dysplasia is an important marker for risk of progression to esophageal adenocarcinoma (EAC) and an indication for endoscopic therapy. However, BE surveillance technique is variable. The aim of this study was to assess the effect of dedicated BE surveillance lists on dysplasia detection rate (DDR).Patients and methods This was a prospective study of patients undergoing BE surveillance at two hospitals – community (UHL) and upper gastrointestinal center (GSTT). Four endoscopists (Group A) were trained in Prague classification, Seattle protocol biopsy technique, and lesion detection prior to performing BE surveillance endoscopies at both sites, with dedicated time slots or lists. The DDR was then compared with historical data from 47 different endoscopists at GSTT and 24 at UHL (Group B) who had undertaken Barrett’s surveillance over the preceding 5-year period. Results A total of 729 patients with BE underwent surveillance endoscopy between 2007 and 2012. There was no significant difference in patient age, sex, or length of BE between the two groups. There was a significant difference in detection rate of confirmed indefinite or low grade dysplasia and high grade dysplasia (HGD)/EAC between the two groups: 18 % (26 /142) Group A vs. 8 % (45/587) in Group B (P  < 0.001). Documentation of Prague criteria and adherence to the Seattle protocol was significantly higher in Group A. Conclusion This study demonstrated that a group of trained endoscopists undertaking Barrett’s surveillance on dedicated lists had significantly higher DDR than a nonspecialist cohort. These findings support the introduction of dedicated Barrett’s surveillance lists.